Relationship between nutritional status, food intake, and sleep quality with blood pressure of member of Posbindu Mawar Kelurahan Kebayoran Lama Selatan - Ropika Agatha (ARGIPA (Arsip Gizi dan Pangan), 2019)
Hypertension is a disease that affects many older adults, with prevalence increasing every year. Hypertension is caused by nutritional status, diet, and less effective sleep quality. The purpose of this study was to determine the relationship between nutritional status, food intake, and sleep quality, with blood pressure in the age group > 45 years in Posbindu Mawar, Kebayoran Lama Selatan. This study used a cross-sectional method with a sample of 47 people taken by the total sampling technique. Weight and height data were taken by anthropometric measurements, blood pressure data were taken using a Sphygmomanometer, dietary data were taken by interview using the Semi-Quantitative Food Frequency Questionnaire Form and sleep quality data were taken using The Pittsburgh Sleep Quality Index (PSQI) Questionnaire. Data analysis techniques used the Chi-Square test. This research resulted in high blood pressure (72.7%), poor sleep quality (61.7%), and normal nutritional status (44.7%). The results showed that sodium intake and sleep quality were related to blood pressure (p<0.05). Whereas nutritional status, fat intake, and potassium intake were not related to blood pressure (p>0.05). Based on this research, the advice given is to provide counseling about balanced nutritional eating patterns, weight monitoring so that nutritional status remains controlled and education about psychological health that is often experienced by the elderly and elderly such as anxiety, depression, and sleep disorders. Keywords: Elderly, Food Pattern, Hypertension, Nutritional Status, Sleep Quality